1987
DOI: 10.1111/j.1365-2672.1987.tb02709.x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of electrophoretic protein patterns of Providencia rustigianii strains from human diarrhoea and other sources

Abstract: Twenty strains of Providencia rustigianii (including the type strain of Prov. friedericiana) have been characterized by one-dimensional SDS-PAGE of cellular proteins. They comprised 12 strains (almost exclusively associated with the intestinal tract) from humans, plus eight largely from the intestinal tract of pig, penguin and environmental sources. The protein patterns, which contained 45-50 discrete bands, were highly reproducible and were used as the basis for two numerical analyses. In the first, which inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 19 publications
2
30
0
1
Order By: Relevance
“…The level of reproducibility achieved in this study was similar to that quoted as acceptable by Jackman [14] and was well above the minimum acceptable value [28]. Previous studies using similar methods have reported levels of at least 93 % similarity between duplicate samples in separate electrophoretic runs [17,21,25,26]. The dendrogram and protein types recognized in the analysis proved to be extremely robust when the computations were repeated using different levels of trace alignment and background subtraction.…”
Section: Reproducibilitysupporting
confidence: 84%
See 1 more Smart Citation
“…The level of reproducibility achieved in this study was similar to that quoted as acceptable by Jackman [14] and was well above the minimum acceptable value [28]. Previous studies using similar methods have reported levels of at least 93 % similarity between duplicate samples in separate electrophoretic runs [17,21,25,26]. The dendrogram and protein types recognized in the analysis proved to be extremely robust when the computations were repeated using different levels of trace alignment and background subtraction.…”
Section: Reproducibilitysupporting
confidence: 84%
“…The 25 t : s q q e s _ N _ { 1 e s I I I q q q q q q q q d q H H I I I _ _ _ _ > z I l I Serotyping and phage typing 0-serotyping and phage typing were performed using methods described previously [10,24]. Isolates were divided on the basis of 0-serotype and were then further sub-divided by phage typing.…”
Section: Bacterial Culturesmentioning
confidence: 99%
“…The level of reproducibility achieved in this study was higher than that quoted as acceptable by Jackman [1O] and was well above the minimum acceptable value [26]. Previous studies using similar methods have reported levels of at least 93 % similarity between duplicate samples in separate electrophoretic runs [13,19,23,24]. The dendrogram (Fig.…”
Section: Capsular Serotyping and Phage Typingmentioning
confidence: 70%
“…However, the importance of WCPP for this purpose is differently assessed in the literature. Costas and colleagues [19] think it valuable, Olsen and co-workers [20] found it to be not very convincing at least in the case of S. berta. Similarly the efficiency of FT-IR spectroscopy is not yet unambiguously clarified.…”
Section: Discussionmentioning
confidence: 99%